Aquaporins; Systemic, Functional and Therapeutic Correlations in Health and Disease - Talal Ahmed; Sarah Ghafoor (Journal of the Pakistan Medical Association, 2021)
Background: The aquaporins (AQPs) are transcellular proteins that majorly consist of a tetrametric hour-glass like structure. AQPs have a definitive function in transpositioning of water and solutes across cell membrane. This review provides information regarding structure, expression and functions of AQPs in the human body. The purpose of this review is to provide a comprehensive summary of physiological and pathophysiological correlations related to AQPs and their therapeutic implications. Absence or mutations of different aquaporins are believed to be linked to clinical diseases including Sjogren’s Syndrome, nephrogenic diabetes insipidus, liver dysfunction and obesity. Modern therapeutic techniques are utilizing aquaporins in gene therapy for Sjogren’s Syndrome and cholestasis. In conclusion, this study provides a comprehensive description of localization, function, abnormal clinical conditions and therapeutic implications of aquaporin proteins. Keywords: Classification, Clinical, Human Aquaporins, Localization, Continuous....